THE IMPORTANCE OF THE FUNDAMENTAL PRINCIPLES OF IBN SINA’S TEACHINGS FOR SOLVING MODERN WATER-RELATED ENVIRONMENTAL ISSUES - Berdiev Doniyor (Western European Studies, 2024)
This article examines the impact of Avicenna's (Ibn Sina's) teachings on modern approaches to addressing environmental issues related to water resources. Based on the philosophical and scientific principles established in Ibn Sina's works, the study explores the potential application of his ideas for sustainable water resource management in the context of global climate change and increasing pressure on ecosystems
Keywords: Ibn Sina; ecology; water; sustainable management